Sistem Pendukung Keputusan Pemberian Kredit Pensiun Menggunakan Metode Saw Pada BNI Talang Banjar Jambi - Isabella, Sonia; Sardjono, Sardjono (Jurnal Manajemen Sistem Informasi, 2023)
The provision of pension credit at BNI Talang Banjar Jambi is one of the programs intended for employees of ASN, TNI / POLRI, employees of certain BUMN / BUMD, PT. Asabri, PT. Taspen, and pension institutions that have collaborated with BNI. The decision-making process for providing pension credit is still quite long, for data collection it is still using a form, where data from the form must be input again, this of course makes the process slower, after the customer data is complete, to determine whether it is accepted or not, need more time to be analyzed by analysts, checking customer history, whether there are other loans or not, then checking BI checking, if good then the file goes up to superiors, and it takes more time to wait for the decision. From some of these problems, a research was conducted to analyze and design a decision support system using the SAW method, based on the data that had been analyzed using the SAW method, the names of customers who were accepted and not accepted were obtained, the SAW method was also suitable to assist decision making because the system is not difficult, and easy to understand. The design of the input and output produced is also suitable because it is made as simple and easy as possible to be made in a real system, but in the future it is hoped that there will be further research on the security side of the system.